Inorganic-Salts Assisted Self-Assembly of Pluronic F127-Organosilica into Ordered Mesostructures - Liu, Tingting; Hao, T.; Liu, Jian; Liu, Lihong; Liu, Shaomin (American Scientific Publishers, 2016)
Periodic mesoporous organosilicas (PMOs) have been synthesized through the condensation of organosilicates 1,2-bis(trimethoxysilyl) ethane around inorganic-electrolyte-stabilized Pluronic F127 [(EO)106(PO)70(EO)106] triblock copolymer micelles in a sodium bicarbonate (NaHCO3 /sodium carbonate (Na2CO3 buffer solution (pH ˜ 9 9). It is found that the addition of inorganic sulfate salts in the synthesis is crucial factor to ensure the formation of ordered mesostructures. The addition of Na2SO4 and MgSO4 in the synthesis system can lead to the formation of ordered 2-D hexagonal (P6mm) and 3-D cubic (Im3m) mesostructure, respectively. The effects of other inorganic sulfate salts such as CuSO4, NiSO4, and ZnSO4 have also been investigated. Apparently, the interaction between Pluronic F127 micelle and organosilica oligomers is enhanced by the presence of these inorganic salts. The mechanism for PMOs formation has been proposed on the basis of inorganic salts assisted micelles-organosilicates closed packing under mild synthetic condition. The findings from this work contribute fundamental understanding towards a new formation route of these ordered mesoporous materials, thus providing a new strategy to fabricate mesoporous silicas with controllable structures for emerging applications.